Penerapan Media Pembelajaran manik-Manik Untuk Meningkatkan Hasil Belajar Matematika Siswa: Indonesia - Nofita Tryana; Syahri Ramadhan; Anggi Fitri; Ayu Purnamasari S; Zalisman; Evi Rahayu; Nikmah (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to determine the improvement of student learning outcomes in mathematics subjects counting operations on integers through the media of beads. The method used is Classroom Action Research. The research was carried out in two cycles, each cycle consisting of two meetings, with stages, namely: planning/preparing for action, implementing the action, observing, and reflecting. Data collection techniques using observation techniques, learning outcomes tests, and documentation. Based on the results of the study, it is known that there is an increase in student learning outcomes from before the action, Cycle I, and Cycle II. In the first cycle, only 21 students completed with an average of 62.29. There was an increase in cycle 2 reaching 30 students who completed with an average of 75.71. Thus, the use of beads media can improve student learning outcomes in mathematics.